Differences of terrestrial mammal species diversity between natural forest and edge forest areas in Batutegi Protected Forest, Lampung, Indonesia - Robithotul Huda; Yossa Istiadi; Dolly Priatna (Indonesian Journal of Applied Environmental Studies, 2020)
This research is an explorative quantitative survey by testing differences in species of terrestrial mammals found in natural forest (core) and edge forest (ecoton) areas. The data collection was obtained by using camera traps installed for 3 months based on a grid cell 2 x 2 km, with a total of 16 camera traps placed in core area and another 17 were in ecotone. The object of this research was medium (0.3 kg) to large terrestrial mammals. The t test was used to determine the differences the species diversity of mammals between two research areas. The study shows that there are 22 species of terrestrial mammals with a total of 552 individuals, which is distributed in both research areas. In the core area there are 18 species with 237 individuals, while in the ecotone there are 18 species with 315 individuals. Analyses the species richness index was 17.8171 for the core area while 17.8262 for the ecotone area. Similarity index in both study areas ranged from 0.7106 to 1. While the value of diversity index (Shannon-Wiener) in the core area H '= 2.2038 and in the ecotone area H' = 2.0541. Three species with the greatest relative abundance values are Porcupine (Hystrix brachyura), Barking Deer (Muntiacus muntjak), and Wild Boar (Sus scrofa). Based on the t tests of the two research areas, which are core area and ecotone, obtained tcount 0.41365 (p 0.05), it can be interpreted that the diversity of terrestrial mammals species in the core and ecotone areas is not the same.Penelitian ini merupakan penelitian kuantitatif survei eksploratif dengan melakukan pengujian perbedaan terhadap jenis mamalia teresterial yang ditemukan di wilayah hutan alam (inti) dan wilayah hutan tepi (ekoton). Pendataan mamalia teresterial menggunakan camera trap yang dipasang selama 3 bulan berdasarkan grid cell 2 x 2 km, dengan 16 camera trap dipasang di areal inti dan 17 lainnya di ekoton. Objek penelitian adalah mamalia teresterial berukuran sedang (0,3 kg) hingga mamalia besar. Uji t digunakan untuk menentukan perbadaan keragaman jenis mamalia teresterial pada dua areal penelitian. Hasil penelitian menunjukkan terdapat 22 jenis mamalia teresterial dengan total 552 individu, yang tersebar di kedua areal penelitian. Pada areal inti terdapat 18 jenis dengan 237 individu, sedangkan pada areal ekoton ditemukan 18 jenis dengan 315 individu. Analisis indeks kekayaaan jenis menunjukkan nilai 17,8171 untuk areal inti dan 17,8262 untuk areal ekoton. Indeks kemerataan pada kedua areal penelitian berkisar antara 0,7106 hingga 1.  Sedangkan nilai indeks keragaman (Shannon-Wiener) pada areal inti H’ = 2,2038 dan pada areal ekoton H’= 2,0541. Tiga jenis mamalia teresterial dengan kelimpahan relatif terbesar yaitu Landak (Hystrix brachyura), Kijang (Muntiacus muntjak), dan Babi hutan (Sus scrofa). Berdasarkan uji beda terhadap dua areal penelitian yaitu areal hutan alam (areal inti) dan areal tepi hutan (ekoton) didapatkan thitung 0,41365 (p 0,05), maka dapat diartikan bahwa keragaman jenis mamalia teresterial di areal inti dan ekoton tidak sama.